Development and evaluation of the British English coordinate response measure speech-in-noise test as an occupational hearing assessment tool. (3rd October 2017) - Semeraro, Hannah D.; Rowan, Daniel; van Besouw, Rachel M.; Allsopp, Adrian A.
Abstract: Objective : The studies described in this article outline the design and development of a British English version of the coordinate response measure (CRM) speech-in-noise (SiN) test. Our interest in the CRM is as a SiN test with high face validity for occupational auditory fitness for duty (AFFD) assessment. Design : Study 1 used the method of constant stimuli to measure and adjust the psychometric functions of each target word, producing a speech corpus with equal intelligibility. After ensuring all the target words had similar intelligibility, for Studies 2 and 3, the CRM was presented in an adaptive procedure in stationary speech-spectrum noise to measure speech reception thresholds and evaluate the test–retest reliability of the CRM SiN test. Study sample : Studies 1 ( n = 20) and 2 ( n = 30) were completed by normal-hearing civilians. Study 3 ( n = 22) was completed by hearing impaired military personnel. Results : The results display good test–retest reliability (95% confidence interval (CI) < 2.1 dB) and concurrent validity when compared to the triple-digit test ( r ≤ 0.65), and the CRM is sensitive to hearing impairment. Conclusion : The British English CRM using stationary speech-spectrum noise is a "ready to use" SiN test, suitable for investigation as an AFFD assessment tool for military personnel.